Comparative study of ant communities of rehabilitated mineral sand mines and heathland, Western Australia - Bisevac, L.; Majer, Jonathan (1999)
We conducted a survey of ants in April 1997 in seven rehabilitated (2- to 20-year-old) and three native heathland reference sites of the Renison Goldfields Corporation (RGC) Mineral Sands operations at Eneabba, Western Australia. We employed a variety of collecting methods, including pitfall trapping, litter and soil sampling, sweeping and beating of vegetation, and collecting by hand in the day and after dark, replicating those used by previous researchers in a similar study conducted in the same area in 1980. We found a total of 96 ant species representing 30 genera in 1997, compared with 46 species from 18 genera in 1980. Ant species richness increased with age of rehabilitation and exceeded that of heath controls by the time it reached 11 years. Ant species richness related to rehabilitation age was represented by a logarithmic curve, and the slope for current rehabilitation was steeper than that for the earlier rehabilitation studied in 1980. This probably reflects improved rehabilitation practices. Ordination of the sites in terms of ant species composition indicated differences between ant species in the rehabilitated sites studied in 1980 and 1997, and also between all rehabilitated sites and heath controls. Classification of the sites in terms of the distribution of ants across functional groups also indicated differences between rehabilitation and heath control sites. According to species composition and functional group profiles from rehabilitated and control sites, we concluded that although the current rehabilitation allows for a rapid return of ant species, even after 20 years the fauna still had not attained the composition of the original heath fauna.